Efficacy of MRI in primary care for patients with knee complaints due to trauma: protocol of a randomised controlled non-inferiority trial (TACKLE trial) - Swart, Nynke M (BioMed Central, 2014)
BACKGROUND: Patients with traumatic knee complaints regularly consult their general practitioner (GP). MRI might be a valuable diagnostic tool to assist GPs in making appropriate treatment decisions and reducing costs. Therefore, this study will assess the cost-effectiveness of referral to MRI by GPs compared with usual care, in patients with persistent traumatic knee complaints. DESIGN AND METHODS: This is a multi-centre, open-labelled randomised controlled non-inferiority trial in combination with a concurrent observational cohort study. Eligible patients (aged 18–45 years) have knee complaints due to trauma (or sudden onset) occurring in the preceding 6 months and consulting their GP. Participants are randomised to: 1) an MRI group, i.e. GP referral to MRI, or 2) a usual care group, i.e. no MRI. Primary outcomes are knee-related daily function, medical costs (healthcare use and productivity loss), and quality of life. Secondary outcomes are disability due to knee complaints, severity of knee pain, and patients’ perceived recovery and satisfaction. Outcomes are measured at baseline and at 1.5, 3, 6, 9 and 12 months follow-up. Also collected are data on patient demographics, GPs’ initial working diagnosis, GPs’ preferred management at baseline, and MRI findings. DISCUSSION: In the Netherlands, the additional diagnostic value and cost-effectiveness of direct access to knee MRI for patients presenting with traumatic knee complaints in general practice is unknown. Although GPs increasingly refer patients to MRI, the Dutch clinical guideline ‘Traumatic knee complaints’ for GPs does not recommend referral to MRI, mainly because the cost-effectiveness is still unknown. TRIAL REGISTRATION: Dutch Trial Registration: NTR3689.